2009
DOI: 10.1021/cm9027447
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Copper Acetamidinate ALD Precursors on Nickel Surfaces

Abstract: The adsorption and thermal activation of copper(I)-N,N 0 -di-sec-butylacetamidinate on a Ni(110) single-crystal surface were characterized in connection with the use of that compound as a precursor for the growth of copper films via atomic layer deposition (ALD) processes. Studies were carried out under ultrahigh vacuum (UHV) conditions by using a combination of X-ray photoelectron spectroscopy (XPS), low-energy ion scattering (LEIS), and temperature-programmed desorption (TPD). A temperature window between ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 36 publications
4
80
0
1
Order By: Relevance
“…Finally, our initial work on the deposition of the same copper precursor on a Ni(110) single-crystal surface identified a temperature window between approximately 350 and 450 K for the deposition of the precursor on the surface: lower temperatures are insufficient for activation of the dissociative adsorption, and higher temperatures lead to continuous decomposition beyond Cu monolayer saturation. 15 That study also suggested more complex surface chemistry than on SiO 2 . Here, we provide further details on the thermal conversions involved.…”
Section: -3 -mentioning
confidence: 78%
See 4 more Smart Citations
“…Finally, our initial work on the deposition of the same copper precursor on a Ni(110) single-crystal surface identified a temperature window between approximately 350 and 450 K for the deposition of the precursor on the surface: lower temperatures are insufficient for activation of the dissociative adsorption, and higher temperatures lead to continuous decomposition beyond Cu monolayer saturation. 15 That study also suggested more complex surface chemistry than on SiO 2 . Here, we provide further details on the thermal conversions involved.…”
Section: -3 -mentioning
confidence: 78%
“…15 Less clear is what may happen if the temperature used in ALD is high enough to promote the second set of reactions reported here. As indicated in Figure 4, the copper atoms start to be reduced on the surface at temperatures slightly above 300 K, a change that is quite extensive by In view of this emphasis of the need to use a hydrogenation agent in the second half of the ALD cycle, it is particularly important to identify the thermal chemistry of the ALD precursor and to evaluate the feasibility of being able to remove any possible intermediates that may form on the Q. Ma, R. G. Gordon, and F. Zaera, Surface Chemistry of Copper(I) Amidinates in...…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations